Vesicle-micelle transition in aqueous mixtures of the cationic dioctadecyldimethylammonium and octadecyltrimethylammonium bromide surfactants - Alves, Fernanda Rosa (2007)
The vesicle-micelle transition in aqueous mixtures of dioctadecyldimethylammonium and octadecyltrimethylammonium bromide (DODAB and C18TAB) cationic surfactants, having respectively double and single chain, was investigated by differential scanning calorimetry (DSC), steady state fluorescence, dynamic light scattering (DLS) and surface tension. The experiments performed at constant up to 1.0 mM total surfactant concentration reveal that these homologue surfactants mix together to form either mixed vesicles and/or micelles, or both of these structures in equilibrium, depending on the relative amount of the surfactants. The main transition melting temperature Tm of the mixed DODAB-C18TAB vesicles is larger than that for the neat DODAB in water owing to the incorporation of C18TAB in the vesicle bilayer, however, little amount of C18TAB having a minor effect on the Tm of DODAB. The surface tension decreases sigmoidally with C18TAB concentration and the inflection point lies around xDODAB ≈ 0.4, indicating the onset of micelle formation owing to saturation of DODAB vesicles by C18TAB molecules and formation of vesicle structures. At low C18TAB concentrations When xDODAB > 0.5 C18TAB molecules are mainly solubilized by the vesicles bilayers, while at high C18TAB concentrations but when xDODAB < 0.25 micelles are dominant. Fluorescence data of the Nile Red probe incorporated in the system at different surfactant molar fractions indicate the formation of micelle and vesicle structures. These structures have apparent hydrodynamic radius RH of about 180 and 500-800 nm, respectively, as obtained by DLS measurements.